Mature Cystic Teratoma Hiding in the Retroperitoneum of an Adult - Yardesh Singh; Shamir O. Cawich; Thivy Kuruvilla; Sidiyq Mohammed; Ammiel Arra (Case Reports in Oncological Medicine)
We report a rare case of a mature cystic teratoma found in the retroperitoneum of a 28-year-old woman with vague symptomatology. We review the radiologic and pathologic features of this rare lesion.